O schematach ujmowania bliskiej i dalszej przeszłości. W kręgu metodologicznej refleksji historyczno-teoriopolitycznej - Janowski, Karol B. (Przegląd Politologiczny, 2018)
The author considers the manners of discussing the past that result from an analysis of recent publications, celebrations of anniversaries, or conferences, which concern the prerequisites and uniqueness of the political transformation started in 1989. They very frequently bridge the time between the interwar period and the time following the ‘round table,’ implying an ideological and political connection between them, while bypassing the period of the Polish People’s Republic. The perception of the past in this particular manner converges with the ideological and political trends dominating in recent Polish politics. They are exemplified by the following: 1. Glorification of the interwar period. This trend officially emerged in 1989 accompanying the political transformations and has since intensified and weakened alternately. On the one hand, it is a manifestation of a kind of schizophrenia, on the other, it signifies a conscious resorting to myths, as well as the manipulation of the past; 2. Disparagement of the period of the Polish People’s Republic, mixing the truth with half-truths and falsehoods. This is done for the benefit of uneducated recipients, whereas among the intelligentsia stereotypes of totalitarianism, communism, and post-communism prevail; 3. Contrasting the period after 1989 with the period of the Polish People’s Republic. As was the case in the ancien régime, there prevails a tendency to disrupt developmental continuity. The Polish People’s Republic is a ‘black hole’ in Polish history. Secondly, in contrast to the historical truth, the 1989 breakthrough appears as an event in which the ancien régime had a minute or no contribution whatsoever; alternatively this is presented as a factor that delayed the ‘true’ overthrow. This manipulation falls inside the scope of activities of the ‘Ministry of Truth’ from Orwell’s 1984. General conclusions. There is a lack of reflection, which remains in contrast to the requirements of objective description and the analysis of political phenomena and processes, an insufficient knowledge of political doctrines, a cognitive laziness, conformism and Fabianism, an intellectual avoidance of more profound analysis, a succumbing to the power of ‘political correctness,’ and a ‘herd instinct’ which epitomizes approaches to discussing both the immediate and distant past referred to in the paper.